Soil organic carbon stocks and fractionation under different land uses in the Peruvian high-Andean Puna - Rolando, J.L.; Dubeux, J.C.; Pérez, W.; Ramírez, D.; Turin, C.; Ruíz Moreno, M.; Comerford, N.; Mares, V.; García, S.; Quiróz, R. (Elsevier, 2017)
Soil organic C (SOC), the largest terrestrial C pool, has been shown to be sensitive to agricultural disturbance. In the Andean Puna, agricultural expansion is thought to be jeopardizing the large SOC stock sequestered in its soils. In this paper, we assessed the impact changes in land use have on C sequestration, fractionation and δ13C natural abundance featuring two case studies in the Peruvian Central Puna. We found SOC stocks greater than average temperate grassland soils (between 123 ± 4 and 136 ± 4 Mg C ha− 1 in the 0–30 cm soil profile); however, they did not differ between land uses. In the first case study, depletion of δ13C in mineral associated C in long fallow (> 7 yr) and maca (Lepidium meyenii Walpers) croplands was hypothesized to be caused by disruption of soil aggregates due to tillage and initial greater SOC concentration in maca plots. In addition, SOC loss was found in long fallow plots, and was correlated to steep and low plant cover plots; evidencing that soil degradation does not occur during cropping activity but due to erosion after land abandonment. In the second case study, a long-established perennial ryegrass (Lolium perenne L.) - white clover (Trifolium repens L.) association (> 40 yr) was studied. We did not find an increase in SOC stock under the cultivated pasture. However, we found a better soil aggregation and an increase of 17.3 and 12.2 g C kg− 1WSA in particulate organic C, and SOC within small macroaggregates in cultivated pasture soils. Soil δ13C natural abundance was about 1‰ depleted in all measured C fractions of cultivated pastures when compared to native grasslands, suggesting that pasture-fixed C forms labile and recalcitrant SOC fractions.